The Implementation of Parking Management and Its Regulation - Sylvester Enricho Mahardika; Retno Saraswati (Wacana Hukum, 2020)
This study aims to determine the implementation of Local Regulation No. 16/2016 concerning the Implementation of Parking in the City of Pekalongan and to know the obstacles in the implementation and how to solve the problem. The author uses the method of sociological juridical approach that emphasizes descriptive analytical research related to the implementation of Local Regulation No. 15/2016 whether it is appropriate or not. The study provided results in the form of several obstacles in the implementation of Local Regulation No. 16 of 2016, namely 1) tariff setting; 2) orderly arrangement of tariffs; 3) the number of illegal unlicensed parking lots; and 4) lack of orderliness in retribution.Keywords: Local Regulations, Parking, Pekalongan.